Markers of futurity in Old English and the grammaticalization of shall and will - Wischer, Ilse (Adam Mickiewicz University, 2006)
This paper examines the use of potential source lexemes of future markers in Old English, such as willan, sculan, beon and weorþan. First their frequency is analysed in a selection of texts from the OE part of the Helsinki Corpus and compared to the frequency of their cognate forms in Old High German. This quantitative analysis is followed by an examination of the use of these verbs in their respective construction types. In this way it will be demonstrated why in Old English willan and sculan were more suitable candidates for grammaticalisation as auxiliaries to denote future time than beon and weorþan.